Efficient Programs to Support Businesses During and After Lockdowns. Issue 1 (26th December 2020) - Philippon, Thomas
Abstract: I analyze efficient government interventions to mitigate financial distress during a severe macroeconomic downturn. At the macroeconomic level, the key variable is the gap between the real wage and the shadow cost of labor. This gap is large when unemployment is high. At the micro level, laissez-faire leads to excessive liquidation of businesses but an indiscriminate bailout prevents efficient reallocations and implies a large transfer from taxpayers to existing private creditors. I show that a cost-efficient intervention can be achieved with a continuation premium, whereby the government agrees to reduce its claims by the same haircut as private creditors plus a fixed premium. ( JEL D24, G33, G38, H12) Received November 17, 2020; editorial decision November 23, 2020 by Editor Andrew Ellul.